2016
DOI: 10.1590/1678-4324-2016150354
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Oral Administration of Rosmarinus Officinalis Leaves Extract on Rat's Hippocampus which Exposed to 6-Hydroxydopamine

Abstract: Carnosic acid, a diterpene of Rosemarinus officinalis leaves extract (RE), has potent antioxidant activity in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…rosmarinic and ferulic acid, because interactions between different compounds can exist in a synergistic way to reduce free radicals. Besides, other phenolics not identified as carnosic acid, a diterpene of R. officinalis, has potent antioxidant activity in vitro [38].…”
Section: Discussionmentioning
confidence: 99%
“…rosmarinic and ferulic acid, because interactions between different compounds can exist in a synergistic way to reduce free radicals. Besides, other phenolics not identified as carnosic acid, a diterpene of R. officinalis, has potent antioxidant activity in vitro [38].…”
Section: Discussionmentioning
confidence: 99%
“…Although most research on the rosemary herb has contemplated its biologically active essential oil, in the past decade R. officinalis aqueous extracts as well as their corresponding water-soluble isolated compounds have been extensively investigated. In addition to expanding knowledge about known medicinal properties of rosemary extracts, which includes antiproliferative and anti-cancer (Petiwala & Johnson, 2015;Shrestha, Song, Kim, Lee, & Cho, 2016;Tai, Cheung, Wu, & Hasman, 2012), anti-inflammatory (Gonçalves et al, 2018;Lucarini et al, 2013), analgesic (Lucarini et al, 2013), neurodegenerative (Rasoul, Maryam, Taghi, & Taghi, 2016), anti-infective (Andrade et al, 2018) and antioxidant (Wollinger et al, 2016;Gonçalves et al, 2018) effects, other biological activities have been reported. A rosemary water-soluble extract, for instance, showed a great potential as antimatrix metalloproteinase-1 agent in human dermal fibroblasts and reconstructed skin, thus figuring a promising ingredient for the prevention of skin photo damage (Martin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental study was divided into two phases: the nootropic phase (before scopolamine) to test the effectiveness of both oil extracts on the memory process, and the therapeutic phase (after induction of amnesia by scopolamine) to assess the anti-dementia potential activity of both oil extracts. During the experiment, the adopted therapeutic doses of oils were determined according to previous studies of LD50 and therapeutic doses of the two oils [ 36 , 37 ]. Nevertheless, a pilot study was carried out using six rats which revealed that the doses used for single and combined oils were safe.…”
Section: Discussionmentioning
confidence: 99%